Innovative Approaches to Teaching Arabic Vocabulary at PQA Elementary School in Malang City: Implementing the BCM Strategy - Sa`diyah, Halimatus; Suyuti, Suyuti (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This study aims to explore the innovation of Arabic vocabulary teaching variations using the BCM strategy with first and second-grade elementary school students at PQA elementary school in Malang City. The study employed a qualitative method with a case study approach. Data were collected through observations, interviews, and documentation involving teachers and students at the research site. The results show that the implementation of the BCM strategy significantly improved students’ vocabulary comprehension, with "hiwayaty" reaching 100% and "al-bait" reaching 94.44%. The strategy also sparked students’ interest in learning, with 100% participation in singing, 88% in playing, and 75% in storytelling. Gamification emerged as the most widely used method (45%), followed by singing (30%) and storytelling (25%). The implications of this study suggest that the BCM strategy can be implemented as an innovative method to enhance Arabic vocabulary mastery in elementary schools. Interactive activities such as playing, storytelling, and singing were shown to significantly increase student participation. This approach also supports student-centered learning, catering to diverse learning styles. Furthermore, teacher training in the application of BCM can strengthen the effectiveness of teaching. This study opens opportunities for further research on the application of the BCM strategy in other linguistic aspects across different educational levels.